Spectral properties of German and Danish sibilants - Andersen, Preben (Annual Report of the Institute of Phonetics University of Copenhagen, 1976)
The Danish sibilants s and ʃ are normally placed auditorily between German s and ʃ in regard to clearness versus darkness. This distribution also seems to be meaningful as regards their acoustic properties. A partial overlapping is often observed between spectra of Danish s and ʃ, whereas the German spectra are always clearly discernible. The spectral shape of the Danish sibilants, especially that of s, seems to be very sensitive to the parameter rounding/non-rounding of a preceding vowel, and occasionally these spectral differences are greater than those between sibilants belonging to different phonemic categories. Danish and German sibilants can be distinguished by their spectral composition. The Danish sibilant spectra normally show two energy maxima, one in the lower and one in the upper part of the frequency range. German spectra normally show but one energy maximum located in the middle of the frequency range for s and in the lower fifth of the frequency range for ʃ.